ANALYZING THE FACTORS OF STUDENTS’ DIFFICULTIES IN SPEAKING ENGLISH IN JUNIOR HIGH SCHOOL 3 SORONG REGENCY - Fatimah, Wahyu Siti (Pascasarjana IAIN Sorong, 2025)
This study investigates the linguistic, psychological, and pedagogical factors contributing to 80 students as a sample who experienced difficulties speaking English at SMP Negeri 3 Kabupaten Sorong through a mixed-methods approach. Quantitative data from a speaking test revealed that most students could convey general meaning, but they demonstrated significant inaccuracies in vocabulary and grammar. Specifically, 66.25% of participants produced understandable but structurally flawed sentences, while 73.75% exhibited basic grammatical and lexical errors. These results indicate limited mastery of sentence structure and active vocabulary. Complementing the quantitative analysis, qualitative data obtained through interviews uncovered additional barriers such as low motivation, anxiety, limited vocabulary retention, and lack of speaking practice. Psychological factors, including fear of making mistakes, low self-confidence, and negative perceptions of English, emerged as key inhibitors of oral performance. However, the presence of supportive teachers, peer encouragement, and engaging classroom activities like games positively influenced students’ motivation and willingness to participate. Findings also highlight the role of parental support and exposure to English media as informal contributors to language acquisition. This study underscores the importance of integrating communicative, game-based, and contextually relevant approaches to English instruction. It advocates creating safe, motivating environments to reduce anxiety and foster active student engagement. These insights contribute to a more comprehensive understanding of the multifaceted nature of speaking challenges in EFL contexts and inform strategies for enhancing oral proficiency in secondary education settings.